The impact of drug shortages on drug prices: evidence from China - Hu, Shuchen; Zhang, Jinwei; Li, Jianwei; Zhang, Jieqiong; Pan, Mengyuan; Xiang, Cheng; Dave, Chintan V.; Yang, Caijun; Fang, Yu (Frontiers in Public Health, 2023)
Introduction Drug shortages pose a serious global public health challenge, affecting China and other countries. Evidence from USA shows that short-supplied drugs demonstrated a very high price growth during and after a shortage. However, the effect of shortages on drug prices in China remains unknown. This paper aims to understand the impact of drug shortages on prices and explore implications for shortage prevention policy. Methods We collected the purchase prices and delivery rates of 120 drugs from April 2019 to December 2021 across whole China. We examined price progression of affected drugs using linear mixed-effects models and performed subgroup analyses based on the number of manufacturers and the severity of shortage. Results Non-shortage cohort had an annual price growth of 11.62% (95% confidence interval [CI] 8.34 to 14.98). Shortage cohort demonstrated an annual price growth of 8.08% (95%CI 0.12 to 16.77) in the period preceding a shortage, 27.57% (95%CI 6.17 to 52.87) during a shortage, and 9.38% (95%CI −12.64 to 36.39) in the post-shortage period. Drug shortages’ impact on prices varied across subgroups. Compared with that of drug markets supplied by a single manufacturer, the price growth rate of markets supplied by more than one manufacture declined more after the shortage resolution. Conclusion Shortages resulted in significant price increases of study markets, especially the low-priced markets, while the shortage resolution slowed the growth. The primary shortage driver has shifted from the low price to others drivers, such as unavailability of active pharmaceutical ingredients. For currently sole-supplied drugs, the expedited review of applications from other manufacturers should be considered.